ผลกระทบทางด้านกฎหมายต่อประเทศไทยจากการเข้าเป็นภาคีอนุสัญญาว่าด้วยสิทธิคนพิการ ค.ศ. 2006 - อลิสา ด้วงผึ้ง (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Violations of rights of persons with disabilities are one of the major types of human rights violations. The Convention on the Rights of Persons with Disabilities (CRPD) was drafted, endorsed by the United Nations General Assembly with the main objective to promote, protect, and ensure full enjoyment of human rights by persons with disabilities on the equal basis with others. Main principles of the Convention include approaches of protection and disability rights. Having ratified the Convention, a State Party is legally bound to implement and abide by the obligations laid out in the treaty, which are seen as the minimum standards in protection of rights of persons with disabilities. Besides, in order to ensure effective rights protection, ratifying countries will have to adapt their domestic legislation to be harmonized with the objectives and intention of the Convention, as well as to impose measures deemed necessary to reconcile disabled individuals who have been abused or neglected. Moreover, an inter-governmental mechanism which consists of independent experts to monitor implementation of the Convention by the States Parties is also incorporated in the Convention. Results of the study indicate that by ratifying the Convention, Thailand has witnessed considerable improvements in human rights promotion and protection. Domestic legislation involved has been amended, new measures have been employed, and additional mechanisms have been established in order to meet the international standards and be harmonized with the Convention.